Aromatic dithiolate nickel complexes bearing N-substituted bis(diphenylphosphanyl)amine: Synthesis, characterization, and electrocatalytic performance for hydrogen evolution. (15th November 2018) - Deng, Cheng-Long; Zhang, Dong-Liang; Xie, Bin; Lai, Chuan; He, Lin-Xin; Hu, Shu-Peng; Li, Yu-Long; Wu, Yu; Feng, Jian-Shen; Zou, Li-Ke; Mou, Wen-Yu; Wei, Jian
Graphical abstract: Six new aromatic dithiolate nickel complexes [RN(PPh2 )2 Ni(bdt)] and [RN(PPh2 )2 Ni(tdt)] have been synthesized and fully characterized. The nickel atom adopts a slightly distorted square-planar coordination by RN(PPh2 )2 and dithiolate ligands. All complexes can electrocatalyze protons reduction to H2 in the presence of FTA. Abstract: Six aromatic dithiolate nickel complexes bearing N - substituted bis(diphenylphosphanyl)amine (RN(PPh2 )2 ) ligands, [RN(PPh2 )2 Ni(bdt)] (bdt = 1, 2-benzenedithiolate; R = (CH2 )3 OCH3 (1 ), (CH2 )3 SCH3 (2 ), CH(CH3 )C6 H5 (3 )) and [RN(PPh2 )2 Ni(tdt)] (tdt = 3, 4-toluenedithiolate; R = (CH2 )3 OCH3 (4 ), (CH2 )3 SCH3 (5 ), CH(CH3 )C6 H5 (6 )), have been synthesized in moderated yields by condensations of RN(PPh2 )2 NiCl2 with 1, 2-benzenedithiol or 3, 4-toluenedithiol in the presence of Et3 N at room temperature. All the complexes were fully characterized by elemental analysis, FTIR, NMR ( 1 H, 13 C, and 31 P) spectroscopy, UV–Vis spectrum, and thermo-gravimetric analysis. The crystal structures of complexes1, 2, 3, and5 have been investigated by single crystal X-ray diffraction. The nickel atom adopts a slightly distorted square-planar coordination by two phosphorus atoms of RN(PPh2 )2 and two sulfur atoms of aromatic dithiolate ligands in their structures. Furthermore, the electrochemical behaviors of complexes1 –6 and their catalytic activities for electrochemical hydrogen evolution in CH2 Cl2 solution with trifluoroacetic acid (TFA) as a proton source have been studied by cyclic voltammetry.